From “doing alone” to “working together”—Research on the influence of spiritual leadership on employee morale - Jiang, Juan; Ye, Zhixiao; Liu, Jing; Shah, Wasi Ul Hassan; Shafait, Zahid (Frontiers in Psychology, 2023)
In the VUCA (Volatile, Uncertain, Complex and Ambiguous）era, people tried to deal with the impact of drastic changes by seeking spiritual solutions. Spiritual leadership is a beneficial attempt to implement organizational strategy and sustainable development by improving employees' personal spiritual needs, stimulating employees' internal motivation, sense of responsibility, and calling in the work process. This paper theoretically proves that spiritual leadership has a significant positive impact on employee morale. The factors of personal self-efficacy and collective interpersonal trust play an intermediary chain role in this impact. At the same time, the questionnaire data from Chinese organizations are used for empirical analysis. The research proves the role of spiritual leadership in improving organizational morale, verifies the specific promotion paths and methods and puts forward that it is necessary to pay attention to improving the spiritual needs of organizational leaders and members in organizational development. Spiritual leadership can improve self-efficacy by impacting individual self-efficacy and interpersonal trust factors that spread from individual to collective level. Then it radiates to the employee morale factor at the organizational level.